2003
DOI: 10.1088/0963-0252/12/2/319
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the electromagnetic fields formed by backward surface waves in an azimuthally symmetric surface wave-excited plasma source

Abstract: The electromagnetic fields and plasma parameters have been studied in an azimuthally symmetric surface wave-excited plasma (SWP) source, by using a two-dimensional numerical analysis based on the finite-difference time-domain (FDTD) approximation to Maxwell's equations self-consistently coupled with a fluid model for plasma evolution. The FDTD/fluid hybrid simulation was performed for different gas pressures in Ar and different microwave powers at 2.45 GHz, showing that the surface waves (SWs) occur along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…The microplasma is probably sustained by surface waves, demonstrated by a numerical model. 15,16,23 To estimate the gas temperature of the microplasma source, i.e., the reservoir temperature of the microthruster, a small amount of nitrogen is added to the argon plasma to observe the rotational spectra. Since electrons are inefficient in providing the rotational energy to molecules owing to their small mass, the population of rotational states is controlled by collisions with heavy particles.…”
Section: A Microplasma Source and Micronozzlementioning
confidence: 99%
See 2 more Smart Citations
“…The microplasma is probably sustained by surface waves, demonstrated by a numerical model. 15,16,23 To estimate the gas temperature of the microplasma source, i.e., the reservoir temperature of the microthruster, a small amount of nitrogen is added to the argon plasma to observe the rotational spectra. Since electrons are inefficient in providing the rotational energy to molecules owing to their small mass, the population of rotational states is controlled by collisions with heavy particles.…”
Section: A Microplasma Source and Micronozzlementioning
confidence: 99%
“…[3][4][5][6][7][8][9] Assuming that plasmas are excited by surface waves, the major feature of such plasmas is that microwaves penetrate into the plasma chamber along the plasma-dielectric interfaces even in the overdense mode and the electron heating occurs in a thin ͑a few millimeters deep or less͒ skin-depth layer, that is, most of the power is absorbed near the interfaces. [10][11][12][13][14][15][16] Such mechanism of the power deposition is a great advantage to generate plasmas in a limited space without magnetic-field confinement. These features would contribute to a simple structure and long-time operation, compared with other conventional thrusters, because the present thruster requires no electrodes, neutralizers, or magnets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Also peoples have used slot antennas for launching of microwave [4][5][6][7][8] for higher densities. In slot antenna configuration, plasma lengths are broadened with decrease in gas pressures.…”
Section: Introductionmentioning
confidence: 99%
“…9 In dielectric-bounded SWP sources, more than 200 W microwave power is injected. [1][2][3][4][5][6][7][8][9][10][11][12] In MVP sources, microwave plasmas are produced along a dielectric-free metal antenna and the surface waves propagate along the plasma-sheath interfaces. In 2005, Kousaka et al 13 at Nagoya University reported a new SWP source which can generate over-dense plasma along the surface of a negative biased metal rod, called metal-antenna surface wave excited plasma (MASWP).…”
Section: Introductionmentioning
confidence: 99%